Penyuluhan Kegiatan Parenting Orang Tua Untuk Meningkatkan Pendidikan Agama Dalam Keluarga Di Desa Batukaras - Aini Ali Agustini; Neneng Nurmalasari; Imas Masitoh; Cristina Sevi Anggita; Sulastri Banyutresna (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2023)
Religious education in the family plays a major role in forming an individual's values, morality and spiritual identity. In Batukaras Village, the challenges in implementing religious education in the family create the need for effective strategies to increase understanding and application of religious values within the family. This dedication aims to explore the potential of parenting counseling as a solution to improve religious education in families in Batukaras Village. The Participatory Action Research (PAR) method is used to involve parents and local communities in the design, implementation and evaluation of parenting education programs that are adapted to the village context and needs. The results of the service show a significant increase in parents' knowledge and skills in educating their children religiously after participating in the parenting counseling program. This parenting counseling provides a stronger moral foundation for future generations in Batukaras Village. These findings provide a positive contribution to the development of religious education in families at the community level, as well as providing insight for further efforts to build a stronger society morally and spiritually. In conclusion, parenting counseling is an effective strategy in improving religious education in families in Batukaras Village.